Access to Household Sanitation During the COVID-19 Pandemic: A Qualitative Study in Dense Settlement Area of Palembang - Dahlia Margareth; Yustini Ardillah; Indah Purnama Sari; Anggun Budiastuti (Jurnal Ilmu Kesehatan Masyarakat, 2022)
During the COVID-19 pandemic, access to sanitation is an important part of preventing COVID-19. Poor sanitation in the household has the potential to cause the spread of disease at the household level. Densely populated settlements are areas with the highest COVID-19 prevalence. The purpose of this research was to describe access to sanitation in households in densely populated residential areas. This study was Qualitative with descriptive design. Information was collected through in-depth interviews with informants and observations of sanitation facilities at the household level. People in densely populated settlements have access to clean water that meets the requirements of clean water for use in their daily life, however, the community had not fully provided hand washing facilities that meet standards, such as not equipped with soap and not having posters of information on how to wash hands. proper hand washing. Provision of temporary waste disposal facilities in community homes hds not met existing standards, such as not made of strong materials, easy to rust, not easy to clean and many are not equipped with covers. Some people did not carry out processing and sorting of waste before finally throwing it into the trash. In addition, the implementation of disinfection was no longer routinely carried out. People can not afford to buy disinfectant. Access to sanitation in densely populated settlements had not been maximally fulfilled, it is necessary to improve the quality of sanitation facilities at the household level